Uma heterotopia pedagógica : práticas bilíngues com alunos surdos em salas multisseriadas - Almeida, Júlia Caroline de Araújo (Universidade Federal de São Carlos, 2017)
From the concept of resistance coined by Michel Foucault, and also, by the configuration of new fields of knowledge in the education of deaf people with the emergence of cultural perspective, the present work had as main objective to analyze pedagogical practices of bilingual teachers working in multi-serialized that has the Libras (Brazilian Sign Language) as the language of instruction in schools located in two municipalities in the state of São Paulo. Inside the work will be presented the configuration of the multi-series deaf classrooms, differentiating them from the old special classrooms. Observed classrooms have deaf students inserted into a bilingual inclusive educational proposal - schools that have adhered to this format have been nominated as bilingual inclusive schools. There were several concerns that guided this work, which are intended to respond to the end of the work. Among them: Can the "Language of Education" rooms (or multisseries of deaf people) be characterized as heterotopic spaces, loaded with resistance to the educational system that govern them?For the teachers working in these classrooms, what are the biggest challenges and how do they consider that they resist the impositions of the teaching system that govern them and re-signify their pedagogical practices? And yet, how much has Libras been, in fact, language of instruction and composed new practices, plural and resistive in the common school? For that, a qualitative research was developed with investigative proposals of the school routine, therefore, a field research. Observations were made about the daily life of these classrooms and about the performance of teaching, as well as interviews with participating teachers to better understand the educational process and concerns about the study. The everyday research brings with it a unique way of searching and problematizing, with specific procedures that emerge in the act of entering the researcher with the place to be researched. It allows a more cohesive analysis of the field being studied and allows the use of several instruments for data collection. In this study, observation was used with records in field diaries and interviews. The challenge was to articulate the genealogical methodological procedure, based on Foucault concepts and its articulation with everyday research. We conclude that the multisseries rooms analyzed, plural and at the same time singular, are heterotopic spaces, loaded with resistance and the militant action of the teachers participating in this study makes possible an education other to these students. The reading of this work, therefore, intends to contribute with educators who also work with deaf students, constantly resist and seek to re-significate their practices always considering the singularities of their students in the educational process.
A pedagogical heterotopia : bilingual practices with deaf students in multi-series rooms
Keywords: Surdez; Sala “Língua de instrução Libras”; Práticas pedagógicas; Heterotopia; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO